2011
DOI: 10.1097/aln.0b013e31823422e8
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Management of Sepsis and the Understanding of Key Immunologic Defects

Abstract: Anesthesiologists are increasingly confronting the difficult problem of management of patients with sepsis both in the operating room and in the intensive care unit. Sepsis occurs in over 750,000 patients in the United States annually and is responsible for more than 210,000 deaths. Approximately 40% of all intensive care unit patients either have sepsis on admission to the intensive care unit or develop sepsis during their stay in the intensive care unit. There have been significant advances in both understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 116 publications
(113 reference statements)
1
80
1
1
Order By: Relevance
“…Thereafter, it has been suggested that the onset of sepsis is accompanied by the activation and inhibition of the immune system (23), with characteristics of abnormal activation predominantly in the early stage, and immunosuppression predominantly in the advanced stage. In addition, the timing and intensity of early immune activation of the body was associated with a range of factors, including the patients' physical status, virulence of pathogenic bacteria and other complicating factors (24). Among patients with refractory sepsis, due to the immunosuppression resulting from a deficiency in the inflammatory factors to activate the adaptive immune system, it is difficult for persistent infections to be controlled (25).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, it has been suggested that the onset of sepsis is accompanied by the activation and inhibition of the immune system (23), with characteristics of abnormal activation predominantly in the early stage, and immunosuppression predominantly in the advanced stage. In addition, the timing and intensity of early immune activation of the body was associated with a range of factors, including the patients' physical status, virulence of pathogenic bacteria and other complicating factors (24). Among patients with refractory sepsis, due to the immunosuppression resulting from a deficiency in the inflammatory factors to activate the adaptive immune system, it is difficult for persistent infections to be controlled (25).…”
Section: Discussionmentioning
confidence: 99%
“…The normal biphasic reaction may be altered when sepsis is present in very old and diseased persons that frequently present a mild phase of SIRS or do not present it at all; in the later stages it seems that immunosuppression is almost always present [7]. Indeed from what has been described it seems that in both the cases sepsis is characterized by an "altered immune response", unbalanced [8] with prevalence of an excessive proinflammatory reaction in the early phase and a prevalent immunosuppression in the late phase [8.] The definition of sepsis based on the recent achievement on this topic could be reconsidered focusing more on the immune status, we propose the sequent definition: " sepsis is the altered immune response to an infectious challenge, either increased or decreased, and followed by a compromised organ function". The passage from the SIRS to the CARS is marked by the phenomenon of LPS tolerance [9]: the prolonged stimulation of TLR4, the specific receptor for endotoxin, by LPS leads to the silencing of proinflammatory genes and to the stimulation of the contra-inflammatory ones through a process of gene reprogramming [10] with increased expression of IL-10, TGF-, and type I IFNs.…”
Section: Introductionmentioning
confidence: 99%
“…Both of them lead to nuclear factor-κB (NF-kB) activation and induction of over 150 inflammatory and procoagulant genes with increased expression of the proinflammatory ILs tumor necrosis factor TNF), IL1, IL6, interferon  (IFN), chemokines and cell adhesion molecules. This phase, named Systemic Inflammatory Reaction Syndrome (SIRS) is followed by a second phase, the compensatory anti-inflammatory response syndrome (CARS), that modulates SIRS through death by apoptosis of immune cells, gene silencing of the pro-inflammatory genes and increased production of the contra-inflammatory ILs IL10, IL4 and TGF [4][5][6] Through this biphasic reaction in the largest part of the cases the homeostasis is re-established. It is possible however that during the proinflammatory phase because of the "cytokine storm"-induced organ damage, further increased through the release by the injured tissue of the endogenous damage-associated molecular pattern (DAMPs or alarmins such as hig mobility group protein B1(HMBG1), hyaluronan, HSP, proteins S100 etc), as more frequently occurs in young and reactive people, or during the contra-inflammatory phase, due to immunosuppression and diffuse infection, death may ensue [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated increased lymphocyte apoptosis in animals and humans with sepsis and its relation to poor outcome (2,(4)(5)(6). Although initial findings were in adults, lymphopenia and apoptosis-associated depletion of lymphoid organs also have a role in sepsis-related death in critically ill children and neonates (7,8).…”
mentioning
confidence: 99%
“…This presentation is usually caused by an initial, severe proinflammatory response. If appropriate and timely treatment can be instituted, patients may survive this stage; however, an antiinflammatory response frequently follows the proinflammatory phase (2).…”
mentioning
confidence: 99%